The Early Reception of Georg Brandes in Germany and France. A Comparative Study - Torben Jelsbak (Acta Universitatis Carolinae: Philologica, 2023)
The publication of Emigrant Literature, the first volume of Main Currents in Nineteenth Century Literature (1872–1890), constituted Georg Brandes’ breakthrough work and the beginning of his career as a European literary critic. However, the work was very differently received in the two major literary cultures of the time, Germany and France. In the German press, Brandes was saluted as a cultural reformer and icebreaker of literary modernity, “a good European and cultural missionary”, as Friedrich Nietzsche called him in a letter from 1887, whereas French critics reacted with much greater skepticism to Brandes’ work. This situation was especially annoying to Brandes as he regarded French literary and intellectual culture as superior to any other culture of the world and more than anything else he longed for recognition from the French literati. The uneven distribution of critical acclaim was a paradox that also affected Brandes’ self-understanding and position as a lcritic. The following article will examine this tension by providing a comparative study of the reception of Emigrant Literature in Germany and France from 1872 to 1893.